Prospective multi-center study of an automatic online seizure detection system for epilepsy monitoring units. Issue 6 (June 2015) - Fürbass, F.; Ossenblok, P.; Hartmann, M.; Perko, H.; Skupch, A.M.; Lindinger, G.; Elezi, L.; Pataraia, E.; Colon, A.J.; Baumgartner, C.; Kluge, T.
Highlights Large prospective multi-center study of an automatic seizure detection system including 205 patients. Comparison between two automatic seizure detection systems using the same prospectively recorded dataset. Performance numbers on the publicly available CHB–MIT dataset and on 310 retrospective patients datasets.